F27. EFFICACY OF MONTHLY EXTENDED-RELEASE RISPERIDONE INJECTIONS (RBP-7000) FOR THE TREATMENT OF SCHIZOPHRENIA: AN ANALYSIS OF INDIVIDUAL PANSS ITEMS. (9th April 2019) - Andorn, Anne; Graham, Jay; Fava, Maurizio; Csernansky, John; Newcomer, John W; Walling, David; Shinde, Sunita; Muma, Gilbert; Heidbreder, Christian
Abstract: Background: RBP-7000 (PERSERIS™), a once-monthly subcutaneous extended-release risperidone formulation approved for the treatment of schizophrenia in adults, was designed to deliver clinically relevant plasma concentrations on the first day of dosing (with no loading or supplemental dosing required) and throughout the 1-month dosing interval. The efficacy of RBP-7000 was established in an 8-week, double-blind, placebo-controlled trial in which significant improvements were observed in Positive and Negative Syndrome Scale (PANSS) total and subscale scores. This post hoc analysis examined the effects of RBP-7000 on the individual items that comprise the PANSS Positive, Negative, and General Psychopathology subscales. Methods: In the 8-week, multicenter, Phase III, double-blind, placebo-controlled, inpatient study (NCT02109562), adults 18–55 years with acute schizophrenia were randomized to monthly injections of placebo (N=112), RBP-7000 90 mg (N=111) or RBP-7000 120 mg (114). Eligible participants were required to have a PANSS total score 80–120 (inclusive) at screening and a score of ≥4 on at least 2 of the following PANSS Positive subscale items: hallucinatory behavior, delusions, conceptual disorganization, suspiciousness/persecution. In a post hoc analysis of this ITT population, a mixed-effects model for repeated measures with no multiplicity adjustments, was used to examine observed changes in the scores of the 30 individual PANSS items from baseline at day 57. Results: Compared with placebo, treatment with either 90 mg or 120 mg RBP-7000 improved 4 out of 7 PANSS Positive items: hallucinatory behavior (90 mg; 120 mg, P<0.001), conceptual disorganization (90 mg; 120 mg, P<0.01), delusions (90 mg; 120 mg, P<0.05), and suspiciousness/persecution (90 mg; 120 mg, P<0.05). Additionally, improvements in hostility (P<0.01) and excitement scores were observed with RBP-7000 120 mg vs placebo (P<0.01). Treatment with RBP-7000 120 mg also improved 2 PANSS Negative item scores (emotional withdrawal [P<0.01] and passive/apathetic withdrawal [P<0.05]), while stereotyped thinking (P=0.054) and difficulty in abstract thinking (P=0.07) trended toward improvement. Both RBP-7000 doses improved 6 of 16 PANSS General Psychopathology item scores vs placebo: depression (90 mg; 120 mg, P<0.001), active social avoidance (90 mg, 120 mg, P<0.05), uncooperativeness (90 mg, 120 mg, P<0.05), poor attention (90 mg, 120 mg, P<0.05), anxiety (90 mg, 120 mg, P<0.05), and tension (90 mg, 120 mg, P<0.05). Improvements in poor impulse control (P<0.001) and somatic concern (P<0.05) were also observed with RBP-7000 120 mg, while the 90 mg dose improved motor retardation (P<0.01). Discussion: Treatment with both 90 mg and 120 mg of RBP-7000 improved the majority of PANSS items. Importantly, treatment with the higher 120 mg dose resulted in improvement on 2 PANSS Negative items, suggesting RBP-7000 may be useful in addressing difficult to treat negative symptoms.